(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study assesses the protective effect of Nyctanthes arbor-tristis (Nyctaginaceae) extracts and in combination with fluoxetine on stress-induced depression in mice. Leaves were extracted using different solvents (petroleum ether, chloroform and hydroethanol) and administered orally for 14 days. These extracts showed significant improvement in the mobility percentage but among these, hydroethanol extract showed better protective effect from day 1 to 14 in both forced swimming and tail suspension test model. Hydroethanol (100 mg/kg) and chloroform (100 mg/kg) extracts with fluoxetine showed synergistic effect when compared with fluoxetine treated group (10 mg/kg) alone at day 7 and 14. Among monoamine levels only hydroethanol extract (400 mg/kg) restored the 5-HT level near to level of fluoxetine-treated group. Hydroethanol extracts with two higher doses showed significant decrease in glucose and triglycerides levels. Clinically, it may useful as antidepressant drug. Video Clip of Methodology: Tail suspension test: 5 min 57 sec Click to watch